Robot-assisted Ivor Lewis Esophagectomy (RAILE): A review of surgical techniques and clinical outcomes - Shen, Tianzheng; Zhang, Yajie; Cao, Yuqin; Li, Chengqiang; Li, Hecheng (Frontiers in Surgery, 2022)
In the past 20 years, robotic system has gradually found its place in esophagectomy which is a demanding procedure in the deep and narrow thoracic cavity containing crucial functional structures. Ivor Lewis esophagectomy (ILE) is a mainstream surgery type for esophagectomy and is widely accepted for its capability in lymphadenectomy and relatively mitigated trauma. As a minimally invasive technique, robot-assisted Ivor Lewis esophagectomy (RAILE) has been frequently compared with the video-assisted procedure and the traditional open procedure. However, high quality evidence elucidating advantages and drawbacks of RAILE is still lacking. In this article, we will review the surgical techniques, both short and long-term outcomes, the learning curve and explicate the current progress and clinical efficacy of RAILE.